Toothed log periodic graphene-based antenna design for THz applications - Farah Mustafa Rasheed; Hussein A. Abdulnabi (Institute of Advanced Engineering and Science, 2022)
This paper proposes a graphene-based toothed log-periodic antenna for the THz frequency region (0.1–10) THz applications. By adjusting the applied DC voltage on the graphene, the antenna's properties, such as bandwidth, radiation pattern operational frequency ranges have been shifted. The chemical potential, surface conductivity, and surface impedance of the graphene are affected by changing applied DC voltage and hence a reconfigurable antenna has been resulting. The suggested antenna's radiating element is from a graphene material and has log-periodic shape, with 50 ohm feed line placed on the grounded silicon dioxide substrate, 1 µm-thick layers of silicon crystalline and alumina on top of the substrate. The antenna is simulated by the computer simulation technology (CST) 2020 software program. The resultant bandwidth (7-10) TH has a return loss of less than -10 when the chemical potential of graphene is 1eV.